The Role of Religion in Understanding Global Conflict and Peace: Study on adolescents in one of the Islamic Boarding Schools in Indonesia - Sabil Mokodenseho; Zainol Hasan; Wily Mohammad (West Science Islamic Studies, 2023)
Within the framework of an Islamic boarding school in Indonesia, this study explores how religion shapes teenagers' perspectives on world violence and peace. 300 individuals were surveyed using a quantitative research design to examine their attitudes toward peace, views of international conflict, and religious beliefs. The findings show that the participants have a strong commitment to Islamic teachings, a sophisticated grasp of international problems, and largely favourable sentiments toward peace initiatives. There is a strong positive correlation between religious beliefs and pro-peace attitudes, according to correlation and regression analyses. These findings have ramifications for educational policies and interfaith activities, as well as providing empirical insights into the conversation on the influence of religion on the viewpoints of adolescents.